Pengaruh Infrastruktur Ekonomi dan Sosial terhadap Pertumbuhan Ekonomi Indonesia, 2015-2019 - Divia Angelina; Krismanti Tri Wahyuni (Politeknik Statistika STIS, 2021)
Compared to the previous period, in 2014, the infrastructure budget in 2015 increased by 62,7%. For five years, this figure continued to grow until 2019 increased by 62%. The increase in the infrastructure budget in President Jokowi's administration is to accelerate economic growth in Indonesia. However, until the end of the first period of his reign, a third of Indonesia's territory still had economic growth below 5%. In addition, almost 60% of Indonesia's economic growth comes from Java. This study aims to analyze the effect of economic and social infrastructure, namely road, electricity, water, health, and ICT infrastructure on economic growth in Indonesia during the 2015-2019. The analysis using panel data regression with the Fixed Effect Model SUR estimation method. The results showed that the five infrastructure variables had a positive and significant impact on economic growth in Indonesia in 2015-2019.